If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 3) + -6x + -4 = 8 + x Reorder the terms: 2(3 + x) + -6x + -4 = 8 + x (3 * 2 + x * 2) + -6x + -4 = 8 + x (6 + 2x) + -6x + -4 = 8 + x Reorder the terms: 6 + -4 + 2x + -6x = 8 + x Combine like terms: 6 + -4 = 2 2 + 2x + -6x = 8 + x Combine like terms: 2x + -6x = -4x 2 + -4x = 8 + x Solving 2 + -4x = 8 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + -4x + -1x = 8 + x + -1x Combine like terms: -4x + -1x = -5x 2 + -5x = 8 + x + -1x Combine like terms: x + -1x = 0 2 + -5x = 8 + 0 2 + -5x = 8 Add '-2' to each side of the equation. 2 + -2 + -5x = 8 + -2 Combine like terms: 2 + -2 = 0 0 + -5x = 8 + -2 -5x = 8 + -2 Combine like terms: 8 + -2 = 6 -5x = 6 Divide each side by '-5'. x = -1.2 Simplifying x = -1.2
| is=3x+28 | | 0=x^2-1.998x+0.998 | | 3[x+12]=5[x+4] | | 7(-2)(5X-8y)= | | -10-x=-13 | | 9z+5-7z=59-7z | | 6x+3-1=26 | | 3(x-2)+x=7(2x+1)-3 | | (3x-2.5)-(2x-2.1)= | | 30=-26-8x | | -7h-17-6+4h=17-h | | x^4=8x^6+128x^2-16 | | 5[2x-3]=3[3x+2] | | (3c-8)-(-5c+3)= | | f^2=-44 | | 2+x=-4x+12 | | 3(2x+-5)=2(3x+-1)-13 | | 28=-9(7h+4) | | -6(5-r)=12 | | 15+-2C=7 | | 2a^2-5a=0 | | 2=-4x+5x+6 | | 4x^2=-16x+4 | | 2.3x+2=12.3x+2.8x-6 | | x+15=10-x+10 | | 3A^2-4AB+B^2=0 | | 3(2x+-5)=2(3x+-1)+7 | | 5x-12=4x+20 | | -4.5x-y=3 | | 0=96x-12x^2 | | x+1.4=1.09x | | 1862=49(p+10) |